PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLE NON EXAMPLE TERHADAP HASIL BELAJAR SISWA DI KELAS V SD - Jesica Septiana Situmorang; Anton Sitepu; Juliana; Patri Janson Silaban (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
This study aimed to determine the effect of the example-non-example type cooperative learning model on students' learning outcomes on the theme of "7 Peristiwa dalam Kehidupan" for grade V students of SD Negeri 067246 Medan Tuntungan in the academic year 2020/2021. The approach used in this study was quantitative, and the samples were selected using a purposive sampling technique from two classes, totaling 58 students. The results indicated that students' learning outcomes after implementing the example-non-example cooperative learning model were in the very good category, with an average score of 80.27. The normality test showed that the significance value of learning outcomes was Lcount ˃ Ltable, namely 0.200 ˃ 0.05, indicating that the data were normally distributed. The homogeneity test obtained a coefficient value of 0.904, meaning rcount ˃ rtable 0.05. Furthermore, the t-test results found tcount ˃ ttable or 2.935 ˃ 1.699; thus, Ha was accepted. These results indicated that the example-non-example type cooperative learning model had a positive and significant effect on students' learning outcomes. Keywords: